2014
DOI: 10.3390/ijerph110606517
|View full text |Cite
|
Sign up to set email alerts
|

Field Survey of Health Perception and Complaints of Pennsylvania Residents in the Marcellus Shale Region

Abstract: Pennsylvania Marcellus Shale region residents have reported medical symptoms they believe are related to nearby Unconventional Natural Gas Development (UNGD). Associations between medical symptoms and UNGD have been minimally explored. The objective of this descriptive study is to explore whether shale region Pennsylvania residents perceive UNGD as a health concern and whether they attribute health symptoms to UNGD exposures. A questionnaire was administered to adult volunteers with medical complaints in a pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 15 publications
(16 reference statements)
0
17
0
Order By: Relevance
“…In terms of risk perception and self-reported health, a survey in Pennsylvania found that 12.5% of participants presenting to a primary care clinic believed UNGD contributed to their current symptoms, and 22% of participants were concerned about UNGD and its harm to health (Saberi et al, 2014). The data obtained for this part of the study did not allow for discerning whether self-reported symptoms differed amongst residents in the three study areas based on their perceptions of resource development exposures and the impact on health; however, this would be beneficial to include in future studies to determine if the level of community concern (risk perception) aligns with the reported health outcomes.…”
Section: Discussion Of Symptoms (Si-65 Outcomes)mentioning
confidence: 99%
See 4 more Smart Citations
“…In terms of risk perception and self-reported health, a survey in Pennsylvania found that 12.5% of participants presenting to a primary care clinic believed UNGD contributed to their current symptoms, and 22% of participants were concerned about UNGD and its harm to health (Saberi et al, 2014). The data obtained for this part of the study did not allow for discerning whether self-reported symptoms differed amongst residents in the three study areas based on their perceptions of resource development exposures and the impact on health; however, this would be beneficial to include in future studies to determine if the level of community concern (risk perception) aligns with the reported health outcomes.…”
Section: Discussion Of Symptoms (Si-65 Outcomes)mentioning
confidence: 99%
“…Stratified random sampling was used in the current study, which represents a methodological improvement over previous studies. Only one other study appeared to use randomised sampling (Coons & Walker, 2008); most others have used purposive sampling or were not clear in the sampling method (McCarron, 2013;Saberi et al, 2014;Steinzor et al, 2013;Subra, 2009Subra, , 2010.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations